ULTRASTRUCTURAL ORGANIZATION OF THE COMPONENTS OF THE LUNG RESPIRATORY DEPARTMENT IN EXPERIMENTAL ACUTE PANCREATITIS - Zaiats, L.M.; Pasichnyk, O.V.; Kreminska, I.B. (World of Medicine and Biology, 2025)
Acute pancreatitis is one of the most urgent problems in abdominal surgery. The relevance of this problem is primarily due to a significant increase in the number of patients with acute pancreatitis. The prevalence and incidence of acute pancreatitis has increased dramatically in recent years. Experiments were conducted on male white rats with arginine-induced acute pancreatitis. Conducted electron microscopic studies showed that in the conditions of simulated acute pancreatitis, a violation of the ultrastructural organization of the components of the respiratory department of the lungs was noted already during the first 6 hours of the experiment. It was found that the most pronounced changes of a dystrophic-destructive nature are observed after 12–24 hours of the study. Erythrocyte sludge, adhesion and aggregation of leukocytes and platelets are found in the lumen of the hemocapillaries of the alveolar wall.